The Strength of Support Big Cities in Southeast Asia as the Basis of Implementing the Sustainable City Concept to Overcome Environment Problems based on Biplot Analysis - Rahmadina, Rizka Firdaus; Ardhani, Belindha Ayu; Aprilianti , Novia Anggita; Mardianto, M. Fariz Fadillah; Cahyono4, Eko Fajar (International Journal of Psychosocial Rehabilitation, 2020)
The high rate of urbanization in various cities is one of the global problems. Based on data from the United Nations (UN), almost half of the world’s total population, which is 3.5 billion people, lives in urban areas. This problem has also become a major factor which causes cities experience decline in its support power. Cities exactly only used 3% of the earth’s land, but they were able to spend 60 - 80 % of energy consumption, and resulted in 75% of carbon emissions. This is the source of urban environmental problems in the world. ASEAN cooperation in the environmental field to realize sustainable cities is one of the strategies in overcoming these. As a basis for implementing right policy of these efforts, a statistical analysis is needed to find out countries with the same level of sustainability and know the dominant problems in ASEAN. This study used secondary data obtained from the ASEAN Foundation which consisted of 2013 city carrying capacity data from 10 ASEAN countries, those are Brunei Darussalam, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand and Vietnam. The results are Laos, Brunei Darussalam and Cambodia have similarities in terms of the forest area and food production index; Malaysia, Myanmar and Vietnam have similarities in terms of the urban population; Vietnam, Philippine and Thailand have similarities in terms of ozone–depleting substance consumption and access to electric; Vietnam, Myanmar, Thailand and Indonesia have similarities in terms of CO2 emission, GHG emission and agricultural land area.